Design of a Wearable, Low-Cost, Through-Wall Doppler Radar System. (5th August 2012) - Agneessens, Sam; Van Torre, Patrick; Declercq, Frederick; Spinnewyn, Bart; Stockman, Gert-Jan; Rogier, Hendrik; Vande Ginste, Dries
Abstract : A novel, low-cost, low-weight, wearable Doppler radar system composed of textile materials and capable of detecting moving objects behind a barrier is presented. The system operates at 2.35 GHz and is integrable into garments, making it well-suited for usage in difficult to access terrain, such as disaster areas or burning buildings. Wearability is maximized by relying on flexible, low-weight, and breathable materials to manufacture the key parts of the system. The low-complexity Doppler radar system makes use of an array of four textile-transmit antennas to scan the surroundings. The beam emitted by this array is right-hand circularly polarized along all scanning angles and provides a measured gain of 9.2 dBi. At the receiving end, textile materials are used to develop an active wearable receive antenna, with 15.7 dBi gain, 1.1 dB noise figure, left-hand circular polarization, and a 3 dB axial ratio beamwidth larger than 50°. Several measurement setups demonstrate that the onbody system is capable of detecting multiple moving subjects in indoor environments, including through-wall scenarios.